Hobbes, law, and public conscience. Issue 1 (2nd January 2016) - May, Larry
Abstract : This paper brings forth the importance of public conscience in Hobbes's account of politics and law. It connects this idea to the famous Martens Clause that played and continues to play a crucial role in international legal debates. The Martens Clause, part of the preliminary materials of the Hague Conventions, posits that humanity's 'public conscience' should play a role in international legal norms concerning warfare when treaties or conventions do not provide guidance. The paper argues that Hobbes also appeals to public conscience in his construction of the relationship between law and politics. Rather than the private conscience that might challenge the sovereign, the public conscience is that which reflects moral principles such as equity which the paper argues is more important than justice in interpreting the law. The paper thus elucidates an important component of Hobbes's theory and makes clear its relevance for international affairs.